هذه صورة سؤال وجواب في علم زوجات رسول الله صلى الله عليه وسلم - قادر ظاهر احمد (مجلة دراسات في التاريخ والآثار, 2020)
The summary Wrote in the biography of the Honorable many ,and wrote the Prophet Muhammad this flag gives every day with new, wrote about his life before and after the mission a lot and there are books about his wives and his fights and there are books of Hadith and literature written by and his birth a childhood, and his mother and grandfather and uncle and wrote about his emigration from Mecca to Medina. What is new in this research, the author could take twenty-three mentions a woman